In House Training “Manajemen Kebidanan Dan Pendokumentasian Asuhan Kebidanan” Bagi Bidan Di Rumah Sakit Kristen Ngesti Waluyo Parakan Temanggung - Nor Tri Astuti Wahyuningsih; Kristinawati Kristinawati; Yochebeth Dewi Zulaihah (Pelita Abdi Masyarakat, 2021)
Background : As Health Workers, of course there are demands and Competency Standards that must be met in carrying out their duties as Midwives. According to the Midwifery Practice Standards, there are 9 (nine) Standards, namely Methods of Care, Assessment, Midwifery Diagnosis, Plans of Care, Action, Client Participation, Monitoring, Evaluation, and Documentation. In conducting Documentation, Midwives must refer to the Standards of Midwifery Care. Based on the recommendation of the competency test results in the recredential activities at the hospital. Kristen Ngesti Waluyo Parakan Temanggung, namely the need for education and training for midwives regarding midwifery management and documentation, so skills improvement activities are planned through In House Midwifery Management Training and Documentation of Midwifery Care. Methods : The activities are carried out using the lecture, Role Play, Small Group Discussion (SGD) method with 4 stages, namely preparation, implementation, evaluation and follow-up plans. Results : In House Training participants as many as 28 people, the results showed that there was an increase in knowledge as many as 26 people (92.9%). Conclusion : After completing the material presentation activities with the lecture method, and exercises through role play activities and Small Group Discussion (SGD) through measuring the Knowledge Level with Pre Test and Post Test, it was found that there was an increase in knowledge about Midwifery Management and Documentation of Midwifery Care. So that this service activity is considered quite effective with the result of an increase in knowledge.